1985
DOI: 10.1007/bf01229822
|View full text |Cite
|
Sign up to set email alerts
|

Thiopyronine and 8-methoxypsoralen sensitized photodynamic effect on DNA synthesis in yeast

Abstract: The synthesis of DNA in growing yeast cells was investigated after photodynamic treatment of the cells with thiopyronine (TP) and visible light or with 8-methoxypsoralen (8-MOP) and UVA light. DNA synthesis was inhibited after photodynamic treatment with 8-MOP but not after photodynamic treatment with TP. This result is further evidence that the photodynamic effect with TP does not attack nuclear DNA in eucaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Comparing these results with similar investigations with yeast (Lochmann et al 1981, Lochmann andRoth 1985), we find the same effect in both cell types, although the necessary concentration of TP is about ten times lower for mammalian cells than for yeast . Comparing these results with similar investigations with yeast (Lochmann et al 1981, Lochmann andRoth 1985), we find the same effect in both cell types, although the necessary concentration of TP is about ten times lower for mammalian cells than for yeast .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Comparing these results with similar investigations with yeast (Lochmann et al 1981, Lochmann andRoth 1985), we find the same effect in both cell types, although the necessary concentration of TP is about ten times lower for mammalian cells than for yeast . Comparing these results with similar investigations with yeast (Lochmann et al 1981, Lochmann andRoth 1985), we find the same effect in both cell types, although the necessary concentration of TP is about ten times lower for mammalian cells than for yeast .…”
Section: Resultssupporting
confidence: 84%
“…In figure 5, it is shown that in yeast cells TP is mostly located in the cell wall or cell membrane . Lochmann et al 1981, 1985, Schiitze 1982, 1984) and indicate the absence of an effect of TP and visible light on nuclear genes also in CHO cells . Schdtze 1982, 1984, Micheler 1972, Lochmann et al 1976) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation